Comparison of User Satisfaction of Mobile-Based Document Scanner Applications on Camscanner and Simple Scanner Using the TAM Method - Restu Apri Yanto; Zarnelly Zarnelly; Megawati Megawati; M.Afdal M.Afdal (UIN Sumatera Utara, 2025)
CamScanner and Simple Scanner users were not very satisfied with the services and performance of their applications. Complaints included annoying ads, technical difficulties, limited features, and problems with the paid version. To analyze user satisfaction, this study used the Technology Acceptance Model (TAM) involving five main variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual Use (AU). This study aimed to compare user satisfaction of both applications. The results showed that for CamScanner, four hypotheses were accepted and one was rejected, while for Simple Scanner, all hypotheses were accepted. This indicates that for CamScanner, 80% of the variables influence user satisfaction, and for Simple Scanner, 100%. In general, this study confirms that perceived ease of use and usefulness of both applications are important factors that shape user attitudes, intentions, and behavior in using document scanning applications.